2020
DOI: 10.1177/0363546520949179
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Long-term Hip Osteoarthritis in Patients With Femoroacetabular Impingement Without Surgical Intervention

Abstract: Background: Femoroacetabular impingement (FAI) is a common cause of hip pain and a known risk factor for hip osteoarthritis (OA) and total hip arthroplasty (THA) at a young age. Unfortunately, little is known about the specific factors associated with an increased risk of OA. Purpose: To (1) report the overall rate of symptomatic hip OA and/or THA in patients with FAI without surgical intervention and (2) identify radiographic features and patient characteristics associated with hip OA. Study Design: Case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…77 If left untreated, FAI reduces the sporting activity level considerably, with a negative effect on the patient's quality of life. 50 Moreover, it may produce labral damage and M || early hip degenerative changes. 25,38 Previous studies have reported that prompt arthroscopic treatment is recommended in patients with FAI.…”
mentioning
confidence: 99%
“…77 If left untreated, FAI reduces the sporting activity level considerably, with a negative effect on the patient's quality of life. 50 Moreover, it may produce labral damage and M || early hip degenerative changes. 25,38 Previous studies have reported that prompt arthroscopic treatment is recommended in patients with FAI.…”
mentioning
confidence: 99%
“…BMI >29 kg/m 2 , increased age, and male sex have all been identified as risk factors for OA progression. 10,16,18…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms included pain, hip clicking, catching, locking, stiffness, restricted range of motion, or giving way. 7 The data collection and preprocessing steps were performed as described by Melgun et al 16…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations